Measurement of Japanese Cedar Pollen-Specific IgE in Nasal Secretions - Hiroshi Sakaida (Allergology International, 2014)
Background: : Japanese cedar pollen (JCP) is the most common allergen for seasonal allergic rhinitis in Japan. Little is known about local production of immunoglobulin (Ig)E in people with or without Japanese cedar pollinosis. The aims of this study were to measure levels of JCP-specific IgE in nasal secretions and determine correlations with levels in serum. Methods: : Forty-six subjects were enrolled in this study, comprising 24 symptomatic subjects, 9 asymptomatic subjects sensitized to JCP, and 13 subjects not sensitized to JCP. Nasal secretions were obtained during a period of Japanese cedar dispersal, and levels of JCP-specific IgE were measured with CAP-fluorescent enzyme immunoassay. Serum JCP-specific IgE and total IgE were also measured using the same method. Results: Among the 46 subjects enrolled, JCP-specific IgE in nasal secretions was measureable in 43 subjects. Irrespective of symptom development, sensitized subjects showed higher levels of JCP-specific IgE in nasal secretions than non-sensitized subjects. A significant moderate correlation was observed between JCP- specific IgE levels in nasal secretions and serum in all 43 subjects. With stratification by subject group, only symptomatic subjects showed a substantial correlation between JCP-specific IgE levels in nasal secretions and serum. Conclusions: : Our results imply a certain association between JCP-specific IgE in nasal secretions and sensitization of Japanese cedar pollinosis. Therefore, levels of allergen-specific IgE in nasal secretions can be used as an alternative diagnostic marker for allergic rhinitis patients.